ANALISIS KORELASI PEMANFAATAN HASIL PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP TINGKAT KELULUSAN MAHASISWA PADA FAKULTAS EKONOMI UNIVERSITAS PAKUAN BOGOR - Satsangkaryon Satsangkaryon (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
ABSTRACTThe development of information technology (IT) is now very rapidly and their impact on student learning can be both positive and negative. From the data graduation in 2009/2010 known to students with graduation "Faster" and "On Time" as much as 32.79%, 21.12% in 2010/2011 and 2011/2012 as much as 25.54% of them with graduation " Too late "and" It's Too late "means the Faculty of Economics Unpak mostly less working hard to speed up graduation. Based on the answers of 100 respondents, namely the Faculty of Economics students in 2009/2010 and 2010/2011 Unpak known as much as 74% stated "quite agree" that they have made use of IT results in the learning process to obtain answers to the exam or the plagiarism and those included in the forecast graduation category of "late" (27%) and "very late" (7%). Those who expressed "quite agree" to abuse the results of IT and categorized behave "moderate" (81%) so that it can be concluded that the abuse of IT results and student behavior are correlated to the level of graduation. Based on the results obtained correlation rs = .242 and P_ value of 0:15 or less than 0.05 and based on regression test result R = 37.9% (R square = 14.4%) so it can be concluded that the rate of Conduct and Level IT misuse has relatively strong correlation to the level of graduation.Keywords: Estimated Graduate Student, Behavior, Information Technology Misuse results